2002
DOI: 10.1038/sj.ejcn.1601510
|View full text |Cite
|
Sign up to set email alerts
|

Phloem fortification in rye bread elevates serum enterolactone level

Abstract: Objective: To analyse the lignan content of phloem powder enriched rye bread and to study the dose -response relationship of the effect of dietary plant lignans derived from phloem on intestinal production of enterolactone by measuring enterolactone concentration in serum. Design: A randomized double-blind supplementation trial. Subjects: Seventy-five non-smoking men recruited by newspaper advertisements. Intervention: Subjects were randomized to three study groups receiving either rye bread high in phloem (HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
2
7
1
Order By: Relevance
“…diet rich in these foods may bring 7-HMR daily intake to as much as 30 mg/d, very close to nutraceutical doses. Moreover, the ENL levels (39 ng/ml) reached in plasma of our mice treated with 3 mg/kg of 7-HMR are quite close to the concentration of ENL that can be found in people consuming conventional northern European diets (14•8 and 12 ng/ml) (20,46) and lignan-fortified diets (21 ng/ml) (47) , but we can realistically hypothesise that it can be found at a higher concentration in people consuming lignan-richer diets with the food components cited above (i.e. Middle Eastern or Mediterranean diets) (48) .…”
Section: -Hydroxymatairesinol Improves Metabolismsupporting
confidence: 80%
“…diet rich in these foods may bring 7-HMR daily intake to as much as 30 mg/d, very close to nutraceutical doses. Moreover, the ENL levels (39 ng/ml) reached in plasma of our mice treated with 3 mg/kg of 7-HMR are quite close to the concentration of ENL that can be found in people consuming conventional northern European diets (14•8 and 12 ng/ml) (20,46) and lignan-fortified diets (21 ng/ml) (47) , but we can realistically hypothesise that it can be found at a higher concentration in people consuming lignan-richer diets with the food components cited above (i.e. Middle Eastern or Mediterranean diets) (48) .…”
Section: -Hydroxymatairesinol Improves Metabolismsupporting
confidence: 80%
“…This is in line with results from the study by Juntunen et al, who observed a decrease in serum ENL concentration from 28 to 12 nmol l (1 when subjects received wheat bread as a substitute for part of their habitual diet (15). Three previous intervention studies found increased serum or plasma ENL levels after the consumption of lignan-rich diets for a period of 3Á/4 weeks (18,19,28). In spite of high dietary fibre contents, the intervention diets led to an increase in serum ENL concentration after 3Á/4 weeks, in contradiction to results of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Three previous intervention studies found increased serum or plasma ENL levels after the consumption of lignan-rich diets for a period of 3Á/4 weeks (18,19,28). In spite of high dietary fibre contents, the intervention diets led to an increase in serum ENL concentration after 3Á/4 weeks, in contradiction to results of the present study.…”
Section: Discussioncontrasting
confidence: 56%